Tingkat Adiksi Game Online Siswa SMPN 13 Padang - Nia Fitri Yanti; Marjohan Marjohan; Rika Sarfika (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The incidence of online game addiction in teenagers of Indonesia is increasing every year. This lead to the impact of teenager’s behavior. This study aims to determine online game addiction level of teenagers in SMPN 13 Padang. The design of this study uses the descriptive analyst. The sample in this study is the students of SMP N 13 Padang with the number of respondent who had online games experience is 88 teenagers by using stratified random sampling. The research instrument used is GASA (Game Addiction Scale Assessment). The results showed that the average online game addiction average score was 63,32 in intermediate level of addiction.  This means that the teenagers of SMPN 13 Padang need to be given an intervention to decrease their addiction level and prevent further negative effect for their productive life. It is suggested that mental nurses can collaborate with the school and the education office to conduct cognitive behavior therapy on an ongoing basis in an effort to prevent online game addiction.